A Comparative Evaluation of Simulation-Based and Traditional Teaching Strategies in Undergraduate Medical students - Sadaf Sajid, Faheed ul Haque, Tariq Javed, Aamer Wadud, Anwar Soomro, Mian Bilal Ahmad , Shahnaz Antara, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
The increasing complexity of modern medical education has intensified the need toidentify teaching methods that enhance clinical competence, critical thinking, and skill retention. This study evaluated the comparative